Global Benchmarking and Best Practices in Islamic Education Management: A Systematic Literature Review - Nurani Nurani; Subandi Subandi; Deden Makbulloh; Ahmad Fauzan (Revenue Journal: Management and Entrepreneurship, 2026)
This study aims to analyze global benchmarking practices and best practices, as well as their implementation in Islamic education management, through a systematic literature review (SLR) approach. In the era of globalization and increasingly fierce competition between educational institutions, benchmarking has become a strategic instrument for improving the quality and competitiveness of madrasas and Islamic boarding schools (pesantren). This study uses the SLR method following the PRISMA 2020 protocol (Page et al., 2021), which includes the stages of identification, screening, eligibility, and inclusion. Data were collected from Scopus, Google Scholar, DOAJ, and Emerald Publishing databases spanning 2020 to 2025. A total of 45 qualitative, quantitative, and mixed-method articles were analyzed thematically. The study identified that the implementation of global benchmarking in Islamic educational institutions is still limited and not yet systematic. Best practices that can be adopted include transformational leadership strategies, integration of digital technology in learning and governance, development of a global competency-based curriculum, total quality management (TQM), and internal and external quality assurance systems. This research provides theoretical contributions to enriching the Islamic-based integrated quality management model and practical recommendations for policymakers and managers of Islamic educational institutions. The study's conclusions emphasize the need to build a culture of sustainable benchmarking and international collaboration to achieve superior and globally competitive Islamic education.